Perancangan dan Pembuatan Aplikasi Retensi Dokumen berbasis Web di PT Bio Farma (Persero) - Apriliani, Allana Dianzah; Mukaram, Mukaram (STMIK Banjarbaru, 2025)
Document retention management at PT Bio Farma (Persero), especially at the Learning and Development Management Department, is still done semi-manually, causing accumulation of archives and delays in document destruction. To overcome this problem, a web-based document retention application was developed using the System Development Life Cycle (SDLC) method of the Waterfall model, through the stages of needs analysis, system design, implementation, testing, and maintenance. System design is done using the Unified Modeling Language (UML), Data Flow Diagram (DFD), and Entity Relationship Diagram (ERD). The application is made with XAMPP and Visual Studio Code, and this application features document input, document search, retention period notification, and destruction history. The test results using the Blackbox Testing method show that all the main features function according to the specifications that have been designed and can be used without errors. The implementation of this application is expected to support digital transformation efforts in archive management in the company.Keywords: Document Retention; Web-based Application; Waterfall; System Development Life Cycle; Digital Transformation AbstrakPengelolaan retensi dokumen di PT Bio Farma (Persero), khususnya pada Departemen Manajemen Pembelajaran dan Pengembangan, masih dilakukan secara semi-manual sehingga menyebabkan penumpukan arsip dan keterlambatan dalam pemusnahan dokumen. Untuk mengatasi permasalahan ini, dikembangkan aplikasi retensi dokumen berbasis web dengan menggunakan metode System Development Life Cycle (SDLC) model Waterfall, melalui tahap analisis kebutuhan, desain sistem, implementasi, pengujian, dan pemeliharaan. Perancangan sistem dilakukan menggunakan Unified Modeling Language (UML), Data Flow Diagram (DFD), dan Entity Relationship Diagram (ERD). Aplikasi dibuat dengan XAMPP dan Visual Studio Code, serta aplikasi ini terdapat fitur input dokumen, pencarian dokumen, notifikasi masa retensi, dan riwayat pemusnahan. Hasil pengujian menggunakan metode Blackbox Testing menunjukkan bahwa seluruh fitur utama berfungsi sesuai dengan spesifikasi yang telah dirancang dan dapat digunakan tanpa error. Implementasi aplikasi ini diharapkan dapat mendukung upaya transformasi digital dalam pengelolaan arsip di perusahaan.